Characteristics and outcomes of older people on antiretroviral therapy in Tlokwe Clinics, South Africa - Mareike Rabe; Huibrecht C. Lion-Cachet; Melaku A. Eyassu (AOSIS, 2020)
Background: South Africa (SA) has a large human immunodeficiency virus (HIV) epidemic but little is known of its effect on those ≥ 60 years of age viz. 'older-persons' living with HIV (OPLWH). Numbers in this age group are increasing and are expected to place a greater strain on existing resources. Objectives: To describe the demographic features and the co-morbidities of OPLWH in Tlokwe. This included an assessment of viral load (VL) suppression and the identification of associations between patient characteristics and clinical outcomes. Methods: A retrospective file review was undertaken to cover the period 01 May 2017 to 30 April 2018. Descriptive statistics were applied to demographic and clinical data and to treatment outcomes. Statistically significant associations were subjected to logistic regression analysis. Results: Of the 191 participants, 111/191 (58.1%) were female and 167/191 (87.4%) were 60 ̶70 years of age. Of the participants, 154/191 (81.9%) were virally suppressed ( 400 copies/mL). Hypertension (n = 106/191, 55.5%) was the most frequently identified co-morbidity. A CD4 cell count of ≥ 350 cells/mm3 at last assessment correlated positively with VL suppression (odds ratio 2.3, confidence interval 1.05-5.02, p = 0.037). Conclusion: Although the level of VL suppression in this cohort was high, greater effort is required to bring this in line with the Joint United Nations Programme on HIV/AIDS (UNAIDS) recommendations viz. 90% viral suppression in PLWH by 2030. Further research is needed to define the evolving long-term needs of OPLWH and to facilitate entry into care of those currently not in care.